PERAN GREEN BRAND SATISFACTION DALAM MEMEDIASI HUBUNGAN ANTARA GREEN BRAND EXPERIENCE DENGAN GREEN BRAND TRUST - Supadmi, Ni Ketut; Seminari, Ni Ketut (E-Jurnal Manajemen, 2017)
The purpose of this study is to clarify the role of green brand satisfaction in mediating the relationship between green brand experience to the green brand trust. The samples that used were 120 peoples who ghatered with non probability sampling method that purposive sampling form. Data were collected by distributing questionnaires directly and using likert scale. Data analysis technique used are comfirmatori factor analysis, path analysis and sobel test. From the analysis showed that green brand experience and green brand satisfaction ware have significant and positif affect on green brand trust. Green brand experience has significant and positf affect on green brand satisfaction. Green brand satisfaction significantly mediates the role between green brand experience to green brand trust. It shows that green brand experience as the main factor that must be caring. It’s importance for the producens to gives good brand experience to their consumers so they can build strong consumers trust on a brand. The purpose of this study is to clarify the role of green brand satisfaction in mediating the relationship between green brand experience to the green brand trust. The samples that used were 120 peoples who ghatered with non probability sampling method that purposive sampling form. Data were collected by distributing questionnaires directly and using likert scale. Data analysis technique used are comfirmatori factor analysis, path analysis and sobel test. From the analysis showed that green brand experience and green brand satisfaction ware have significant and positif affect on green brand trust. Green brand experience has significant and positf affect on green brand satisfaction. Green brand satisfaction significantly mediates the role between green brand experience to green brand trust. It shows that green brand experience as the main factor that must be caring. It’s importance for the producens to gives good brand experience to their consumers so they can build strong consumers trust on a brand.
Keywords: Key word : green brand experience, green brand satisfaction, green brand trust